An updated review of cystic hepatic lesions - Rawla, Prashanth; Sunkara, Tagore; Muralidharan, Pradhyumna; Raj, Jeffrey Pradeep (Clinical and Experimental Hepatology, 2019)
Cystic hepatic lesions are commonly encountered in daily practice. The diagnosis of these lesions ranges from benign lesions of no clinical significance to malignant and potentially lethal conditions. The prevalence of hepatic cyst (HC) has been reported to be as high as 15-18% in the United States. Imaging with conventional ultrasound, computed tomography, magnetic resonance imaging, or contrast-enhanced ultrasound can be used to characterize further and diagnose. The pre-test probability of a diagnosis is highly affected by the patient’s comorbidities and the clinical and laboratory data; thus, imaging studies should be interpreted in the context of the other clinical information for that particular patient. Treatment modalities for hepatic cyst include fenestration, aspiration sclerotherapy, or surgical resection. In the current review, we discuss the pathophysiology, diagnosis, and treatment modalities for various cystic hepatic lesions.